Morality in everyday life developmental perspectives (Cambridge studies in social and emotional development, 1995)
This collection brings together current research on morality in human development. Morality in its various forms is a dominant influence on the conduct and evaluation of day-to-day life. The pervasiveness of the moral domain can be detected in every aspect of social life; moral commitments shape the goals and aspirations of individuals, and moral judgments are apparent in discourse about most forms of human interaction. Two broad themes integrate this book: social context and development. Contexts include interpersonal as well as societal communities and cultures. This volume will appeal to scholars from many disciplines, including psychology, anthropology, education, sociology, law, linguistics, and ethics.